IS WORKPLACE FRIENDSHIP IMPORTANT ON THE RELATIONSHIP BETWEEN EMOTIONAL EXHAUSTION AND ORGANIZATIONAL CITIZENSHIP BEHAVIOR- TAKE PRESCHOOL TEACHER IN TAINAN AS SAMPLES - Chen, Yi-Chen; Sung, Pei-Yu (International Journal of Application on Economics and Business, 2023)
Preschool educators play a vital role in the preschool education system. Therefore, it is very important to know the working conditions of preschool education and the influential factors of its personnel’s attitude and behavior. According to the literature review, it is found that emotional exhaustion has a negative impact on organizational citizenship behavior, and workplace friendship has a moderating effect on the relationship between emotional exhaustion and organizational citizenship behavior. Therefore, this study used preschool teachers in Tainan, Taiwan as samples to investigate the relationship between emotional exhaustion, workplace friendship and organizational citizenship behavior of individuals (OCBI). In this study, 307 valid questionnaires were collected by using the convenience sampling method. The study found the following points: 1. Emotional exhaustion has a negative impact on OCBI; 2. Workplace friendship has a positive impact on OCBI; 3. Workplace friendship has moderating effect on some relationships between emotional exhaustion and OCBI. Finally, some relevant management suggestions were proposed.